Barn av «tre stammers møte»: skiftende narrativer om ‘solgte’ kvenbarn i Nord-Norge - Mathisen, Stein R. (Tidsskrift for kulturforskning, 2023)
This article takes a closer look at a narrative motif relating how Kven children during famine in the Torne valley in the early 1800s Sweden and Finland were ‘sold’ to Norway. These narratives have been told, written, and performed in different media and varied versions from the time when the events took place, and up to the present. Because these versions can be tied to different contexts through a relatively long period of time, and appear in different social and historical surroundings, the genealogy of this specific narrative motif offer analytic challenges. This involves more specific examinations, looking at who told or documented the narratives, in what contexts, and for what purposes and intentions. The analysis reveals how the narrative motifs through time are connected to changing metanarratives concerning the position of ethnic and national minorities in the Norwegian nation state. This has the potential of broadening the understanding of minority relations often communicated through the metaphor of «the meeting of three tribes», as well as sharpening the focus at the history of Norwegianization politics related to ethnic minorities in the Norwegian north.